The Need for Lateral Piriform Rim Augmentation in Patients with Unilateral Cleft Lip/Palate During Alveolar Cleft Bone Grafting - Rahpeyma, Amin (J Maxillofac Oral Surg, 2014)
BACKGROUND: Alveolar bone grafting in unilateral cleft lip/palate (CLP) patients can improve nasal symmetry and facial esthetic. In some cases lateral piriform hypoplasia cannot be compensated by soft tissue thickness of the face, necessitating onlay bone grafting. This study was designed to estimate the proportion of patients among unilateral CLP patients requiring this procedure. MATERIALS AND METHODS: In a retrospective study, unilateral CLP patients with severe paranasal deficiency, who were managed by paranasal augmentation with cortico-cancellous bone graft during the alveolar cleft bone grafting, were included. RESULTS: From 85 unilateral CLP patients treated from 2005 to 2011 in the Oral and Maxillofacial Surgery Department, Mashhad University of Medical Sciences, fourteen patients were treated with lateral piriform augmentation technique. Mean age of the patients at the time of operation was 16 ± 4.8 years. Follow-up period was 2–6 years. CONCLUSION: Concomitant alveolar bone grafting and lateral piriform augmentation is needed at least in 16.5 % of unilateral CLP patients.